(untitled) (Chittagong University Journal of Biological Sciences, 2013)
The microbiological quality of air, surface and working personnel in a pharmaceutical industry was investigated. Bacterial isolates recovered from the processing environment were also identified. Phenol co-efficient of commonly used disinfectants such as sodium hypochlorite, savlon (chlorhexidine gluconate 0.3% w/v and cetrimide 3% w/v), ethanol, methanol and isopropyl alcohol were determined using standard methods against the most predominant organisms. This study reveals that the personnel involved in manufacturing were the main source of contamination and the common organisms found from samples of air, surface, and working personnel monitoring area were Staphylococcus sp., Pseudomonas sp. and Escherichia sp. Among the used disinfectants of this study, sodium hypochlorite showed the highest potency. Phenol coefficient of sodium hypochlorite, savlon, isopropyl alcohol, methanol and ethanol were 5.55 and 4.44; 2.77 and 2.22; 0.22 and 0.33; 0.33 and 0.44; 0.11 and 0.16 for Staphylococcus sp. and Pseudomonas sp., respectively. To reduce the risk of contamination, working personnel should follow the rules of cGMP (current good manufacturing protocol) and the disinfectants should be used in appropriate concentration for the beneficial cost effect of the pharmaceutical industry and also for a clean environment. DOI: http://dx.doi.org/10.3329/cujbs.v5i1.13373 The Chittagong Univ. J. B. Sci.,Vol. 5(1 &2):77-89, 2010